Geometric adventures with self-assembled metal-ligand coordination structures - Fan, Yucong (2024)
Dynamic covalent chemistry (DCC) has become of increasing interest to researchers due to its unique properties in constructing complex three-dimensional structures. Metal-ligand coordination interactions have been used extensively to construct three-dimensional structures due to the well-defined coordination preferences of metal ions. In this work, two linear tridentate ditopic ligands with different side arms; and two tridentate tritopic ligands with a triangular shape, (one with a benzene at its centre and one with a triazine) were used to coordinate with the transition metal ions Fe2+ and Zn2+. The ligands have the same denticity and topicity, however, the self-assembly products of them were different. The linear ligand with the side group further away had the same behaviour when coordinated with Fe2+ and Zn2+. Both Fe2+ and Zn2+ gave two self-assembly products, which were M4L4 squares and M3L3 triangles, presumed to be circular helicates. The other linear ligand with a side group closer to coordination sites was only investigated with Fe2+, where it gave M4L4 squares and M3L3 triangles on self-assembly. Both the triangular ligands gave interesting results with both Fe2+ and Zn2+ ions. Both triangular ligands gave an M6L4 structure (presumed octahedral) and an M9L6 structure (presumed triaugmented triangular prism) with Fe2+ ions. With Zn2+ ions, the ligand with benzene at its centre only gave M6L4 structures (presumed octahedral); the ligand with triazine at its centre gave both an M6L4 structure (presumed octahedral) and an M9L6 structure (presumed triaugmented triangular prism). In this work however, the influence of side arms on the linear ligands still needs further investigation. Future work will also study different metal ions with different coordination geometries. In addition to metal-ligand coordination, the formation of imine bonds is also a common approach to construct three-dimensional structures. In this work, the formation process of an imine cage was studied. Two different diamines were used for the imine condensation reaction. The simplest diamine was ethylene diamine, which has been determined could hold the cage structure together by other researchers. To investigate structural variation within the diamine, another diamine with a gem dimethyl on the linking chain was studied. The results indicated this diamine likely led to the cage structure forming, although further data still needs to be gathered. The host-guest chemistry in this cage system is interesting, with the existence of guest dicarboxylic acids, the cage could be triggered to assemble and disassemble. However, there was insufficient time to study this during the project and this will form the basis of future work.